METODE TWO STAY TWO STRAY UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI INTERPERSONAL - Dea Maulita Putri Rico; Siti Fitriana; Farikha Wahyu Lestari (Jurnal Guru Kita PGSD, 2019)
Abstract: Two Stay Two Stray Method to Improve Interpersonal Communication Abilities. This research is motivated by students who are unable to appreciate friends or other people who are talking, cannot be good listeners, do not speak when meeting other people on the street, do not shake hands with the teacher they meet, students are less able to communicate in good language to the teacher or friend, unable to respond properly when invited to speak. This type of research is a quantitative research design in quasi experimental form of nonequivalent control group design with pre-test model post-test control group design. The population of this research is the students of class XI Accounting 1, XI Marketing 2, XI Animation SMK Muhammadiyah 1 Semarang. The sampling used in this study is cluster random sampling. The data analysis technique used is percentage analysis with t-test. It was concluded that there was an influence of classical guidance with the two stay two stray method on the interpersonal communication of class XI students of SMK Muhammadiyah 1 Semarang.Keywords: Classical Guidance, Two Stay Two Stray, Interpersonal CommunicationAbstrak: Metode Two Stay Two Stray untuk Meningkatkan Kemampuan Komunikasi Interpersonal. Penelitian ini dilatar belakangi oleh siswa yang tidak mampu menghargai teman atau orang lain yang sedang berbicara, tidak bisa menjadi pendengar yang baik, tidak bertegur sapa apabila bertemu orang lain dijalan, tidak berjabat tangan dengan guru yang ditemui, siswa kurang mampu berkomunikasi dengan bahasa yang baik terhadap guru ataupun teman, tidak mampu merespon dengan baik saat diajak berbicara. Jenis penelitian ini adalah penelitian kuantitatif desain quasi experimental bentuk nonequivalent control group design dengan model pre-test post-test control group design. Populasi penelitian ini adalah siswa kelas XI Akutansi 1, XI Pemasaran 2, XI Animasi SMK Muhammadiyah 1 Semarang. Sampling yang digunakan dalam penelitian ini adalah Simple Random Sampling. Teknik analisi data yang digunakan yakni analisis presentase dengan Uji t (t-test). Disimpulkan bahwa ada pengaruh bimbingan klasikal dengan metode two stay two stray terhadap komunikasi interpersonal siswa kelas XI SMK Muhammadiyah 1 Semarang.Kata Kunci: Bimbingan Klasikal, Two Stay Two Stray, Komunikasi Interpersonal.